Internal nitrogen and phosphorus loading in a seasonally stratified reservoir: Implications for eutrophication management of deep-water ecosystems. (1st October 2022) - Sun, Chuanzhe; Wang, Shaoming; Wang, Hongwei; Hu, Xiaokang; Yang, Fanyan; Tang, Mengyao; Zhang, Min; Zhong, Jicheng
Abstract: Water eutrophication is a serious global issue because of excess external and internal nutrient inputs. Understanding the intensity and contribution of internal nitrogen (N) and phosphorus (P) loading in deep-water ecosystems is of great significance for water body eutrophication management. In this study, we combined intact sediment core incubation, high-resolution peeper (HR-Peeper) sampling, and analysis of N and P forms and other environmental factors in the water column and sediments to evaluate the contributions of internal N and P loading to water eutrophication by N and P fluxes across the sediment-water interface (SWI) of the Panjiakou Reservoir (PJKR), a deep-water ecosystem where eutrophication threatens the security of the local drinking water supply in North China. The results indicated that the PJKR showed obvious thermal and dissolved oxygen (DO) stratification in the warm seasons and full mixing in the cold seasons. The mean DO concentration was 9.9 and 3.55 mg/L in the epilimnion and hypolimnion, respectively, in warm seasons and 10.7 mg/L in cold seasons. The sediment acted as a source of soluble reactive phosphorus (SRP), NH4 + -N, and NO2 − -N and a sink of NO3 − -N. The SRP fluxes were 5.28 ± 4.34 and 2.30 ± 1.93 mg m −2 ·d −1 in warm and cold seasons, respectively, and the dissolved inorganic nitrogen (DIN) fluxes were −0.66 ± 47.84 and 44.04 ± 84.05 mg m −2 ·d −1 . Seasonal hypoxia accelerated the release of P rather than N from the sediments in warm seasons, which came mainly from Fe–P and Org-P under anoxic conditions. The strong negative NO3 − -N flux (diffusion from the water column to the sediment) implied an intensive denitrification process at the SWI, which can counteract the release flux of NH4 + -N and NO2 − -N, resulting in the sediment acting as a weak dissolved inorganic nitrogen (DIN) source for the overlying water. We also found that internal N loading accounted for only ∼9% of the total N loading, while internal P loading accounted for 43% of the total P loading of the reservoir. Our results highlight that efforts to manage the internal loading of deep-water ecosystems should focus on P and seasonal hypoxia. Graphical abstract: Image 1 Highlights: The contributions of internal N and P loads in a deep-water reservoir were evaluated. Seasonal hypoxia accelerated the release of P rather than N from the sediments. P release from sediments under anoxic conditions mainly came from Org-P and Fe–P. Internal N accounted for only 9% of the total N load due to a strong nitrate sink. Internal P accounted for 43% of the total P load.